Real-Time and Ultrasensitive Prostate-Specific Antigen Sensing Using Love-Mode Surface Acoustic Wave Immunosensor Based on MoS2@Cu2O-Au Nanocomposites - Yan Yu; Haiyu Xie; Tao Zhou; Haonan Zhang; Chenze Lu; Ran Tao; Zhaozhao Tang; Jingting Luo (Sensors)
Prostate-specific antigen (PSA) is a well-established tumour marker for prostatic carcinoma. In this study, we present a novel, real-time, and ultrasensitive Love-mode surface acoustic wave (L-SAW) immunosensor for PSA detection enhanced by MoS2@Cu2O-Au nanocomposite conjugation. The MoS2@Cu2O-Au nanocomposites were analyzed by SEM, XRD, and EDS. The experiments show a significant improvement in sensitivity and detection limit compared with the previous detection methods utilizing nanogold alone to detect PSA biomolecules. The experimental results show a good linear relationship when the range of PSA concentrations between 200 pg/mL and 5 ng/mL was tested. The experimental results also show good specificity against alpha 1 fetoprotein and L-tryptophan disruptors.